Nine days to Christmas - Ets, Marie Hall, 1895-; Labastida, Aurora (New York : Puffin, 1991)
Ceci, a little Mexican girl, is excited because now she is old enough to buy a pinata for her first Christmas posada, a party given before the holiday.
Caldecott 1960 Medal Winner
4.0
K-3
Keywords: Christmas -- Fiction; Christmas -- Fiction; Caldecott Medal books; Mexico -- Fiction; Mexico -- Fiction